Goodnight moo - Bryan, Mollie Cox, 1963- (Bryan, Mollie Cox, 1963- Buttermilk Creek mystery, 2020)
"With a foster cow in her corral and a new calf on the way, Brynn MacAlister has a lot on her plate. Especially since her micro-dairy farm is hosting the first annual cheesemakers contest at this year's summer fair. A relative newcomer, Brynn's hoping the contest becomes a tradition, bonding her even more strongly to the community. But when a mysterious tractor accident looks suspiciously like murder, Brynn suspects someone is up to no gouda ... Some folks say the lead suspect was just defending his underage daughter from a suitor more mature than a vintage provolone, but Brynn isn't buying it. Especially when another dead body turns up and Brynn's top cheesemaker falls under suspicion. It's enough to make a girl bluer than her best Stilton. But not enough to stop Brynn from getting to the bottom of things. What she discovers is the small town harbors some pretty unsavory characters. And the closer Brynn gets to the killer, the deeper she gets into danger"--Publisher